PELATIHAN KETERAMPILAN PELAYANAN PRIMA BAGI PEMILIK, PENGELOLA HOMESTAY DAN MASYARAKAT DI PULAU HARAPAN, KEP. SERIBU, JAKARTA - Sudrajat, Deny; Iman Sulaeman; Nika Sintesa; Valentina Happy Vanesa (POLITEKNIK LP3I JAKARTA, 2024)
Excellent service has an important role in accommodation businesses such as homestays because it has a big impact on the guest experience and the long-term sustainability of homestays and tourist attractions. This excellent service training aims to increase the knowledge and skills of homestay managers on Harapan Island, Kep Seribu, Jakarta. The method used was training and practice which was attended by 25 homestay managers. Evaluation is carried out by providing a Google form. The test results showed that 96% of participants experienced increased knowledge and skills in excellent service material so that this community service activity could be categorized as successful.